Redefining Irishness in a globalized world : national identity and European integration - BouAynaya, Yaqoub (Emerald Publishing Limited, 2024)
Giving voice to everyday people in Ireland, Redefining Irishness in a Globalized World: National Identity and European Integration covers crucial topics around notions of 'race', ethnicity, citizenship, inclusiveness, regionalism, global-local dynamics, migration, and governmentality. In this multimedia work, author Yaqoub BouAynaya delves into perceived Irishness and how identity in Ireland evolves within an ever-changing society. Yaqoub examines how identity-related values impact individuals' engagement in their perceived social reality and studies their representation at the local, national, European and global levels. Additionally, chapters explore the evolution of nationalism and its connection to the postcolonial Irish nation state in the context of European governance and globalization. Discussing and often deconstructing 'Irish' national identity, the author incorporates still portraits which expose the reader to variations of Irishness. Drawing on focus groups and analysis of transcribed conversations, Yaqoub presents contemporary attitudes towards identity, ethnicity and citizenship within both Irish and global contexts. Reimagining 'Irish' identity on a uniquely intimate level, this richly thoughtful work aspires to a more egalitarian society in Ireland, Europe and beyond, encouraging readers to rethink their own national identities in turn.